Clinical and genetic landscape of neuronopathic gaucher disease in Ukraine: hepatosplenomegaly and diagnostic delay - Nataliia Samonenko; Nataliia Olkhovych; Olena Okhotnikova; Nataliia Gorovenko (Orphanet Journal of Rare Diseases, 2026)
Abstract Background Neuronopathic Gaucher disease (GD types II and III) represents rare and severe phenotypes of glucocerebrosidase deficiency, characterized by neurological involvement and variable systemic manifestations. Data on clinical presentation and genotype–phenotype patterns in Eastern European populations remain limited. Methods We conducted a retrospective cohort study of 92 patients with confirmed Gaucher disease followed at the National Children’s Specialized Hospital “Okhmatdyt” (Kyiv, Ukraine) between 2001 and 2024. Among them, 4 patients had type II and 6 had type III GD. Diagnosis was established by measurement of leukocyte β-glucocerebrosidase activity and molecular analysis of the GBA1 gene. Clinical, laboratory, and imaging data were analyzed descriptively. Results Type II GD presented in early infancy, with symptom onset from birth to 5 months of age (mean age at onset 2.8 ± 2.6 months) and was diagnosed between 5 and 9 months of age (mean 7.0 ± 2.3 months). Initial manifestations included cytopenias, splenomegaly, failure to thrive, and ichthyosiform dermatitis. Hepatomegaly was uncommon at onset, but hepatosplenomegaly was documented in all patients at diagnosis, followed by rapid neurological regression and death by 14 months of age. Type III GD had a mean age at onset of 2.3 ± 1.66 years and a mean age at diagnosis of 13.8 ± 16.87 years, reflecting substantial diagnostic delay. Oculomotor abnormalities were the most frequent presenting manifestations (83%). At diagnosis, all patients exhibited hepatosplenomegaly, cytopenias, and neurological involvement, while liver function remained preserved. Across both phenotypes, GBA1 variant combinations included genotypes predicted to result in very low or absent residual glucocerebrosidase activity, as well as genotypes predicted to retain some residual activity. Severe clinical courses were observed even in patients whose genotypes were predicted to retain residual enzyme activity, suggesting that predicted residual activity alone does not reliably explain clinical severity. Conclusions In this Ukrainian cohort, neuronopathic GD demonstrated distinct clinical trajectories, with rapidly progressive infantile disease in type II and heterogeneous presentation with marked diagnostic delay in type III. Hepatosplenomegaly was a common systemic feature during disease progression, but should not be interpreted as an isolated stratifying sign. Its presence, particularly in combination with early or progressive neurological manifestations, should raise suspicion of neuronopathic GD.